The standard operating procedure for Airmodus Particle Size Magnifier and nano-Condensation Nucleus Counter. (January 2022) - Lehtipalo, K.; Ahonen, L.R.; Baalbaki, R.; Sulo, J.; Chan, T.; Laurila, T.; Dada, L.; Duplissy, J.; Miettinen, E.; Vanhanen, J.; Kangasluoma, J.; Kulmala, M.; et al.
Abstract: Measurements of aerosol particles and clusters smaller than 3 nm in diameter are performed by many groups in order to detect recently formed or emitted nanoparticles and for studying the formation and early growth processes of aerosol particles. The Airmodus nano-Condensation Nucleus Counter (nCNC), consisting of a Particle Size Magnifier (PSM) and a Condensation Particle Counter (CPC) is a versatile tool to detect aerosol particles and clusters as small as ca. 1 nm in mobility diameter. It offers several different operation modes: fixed mode to measure the total particle number concentration with a fixed, but adjustable lower cut-off size and stepping and scanning modes for retrieving size-resolved information of ca. 1–4 nm particles. The size analysis is based on changing the supersaturation of the working fluid (diethylene glycol) inside the instrument, which changes the lowest detectable size. Here we present a standard operating procedure (SOP) for setting up, calibrating and operating the instrument for atmospheric field measurements. We will also present recommendations for data monitoring and analysis, and discuss some of the uncertainties related to the measurements. This procedure is the first step in harmonizing the use of the PSM/nCNC for atmospheric field measurements of sub-3 nm clusters and particles. Highlights: A standard operating procedure (SOP) for Airmodus PSM and nCNC was developed. It describes how to calibrate, set-up and operate the instrument. The SOP is a step towards harmonizing the measurement of sub-3nm particles.